Functionalization of Alkenyl C–H Bonds with D2O via Pd(0)/Carboxylic Acid Catalysis - Camedda, Nicola; Serafino, Andrea; Maggi, Raimondo; Bigi, Franca; Cera, Gianpiero; Maestri, Giovanni (Synthesis, 2020)
We report herein a simple catalytic method for the extensive labeling of alkenyl C–H bonds through the combination of a palladium(0) complex and a carboxylic acid in the presence of deuterium oxide. The reaction can be applied to a variety of terminal alkenes and the best results are obtained with aryl-substituted examples. This method represents a convenient approach for the preparation of extensively labeled chemicals from the cheapest and safest source of deuterium.
Keywords: palladium; hydrides; deuterium; C–H functionalization; alkenes; catalysis